Rethinking children’s physical activity interventions at school: A new context-specific approach - Jago, Russell; Salway, Ruth; House, Danielle; Beets, Michael; Lubans, David Revalds; Woods, Catherine; de Vocht, Frank (Frontiers in Public Health, 2023)
Physical activity is important for children’s health. However, evidence suggests that many children/adolescents do not meet international physical activity recommendations. Current school-based interventions have had limited effect on physical activity and alternative approaches are needed. Context, which includes school setting, ethos, staff, and sociodemographic factors, is a key and largely ignored contributing factor to school-based physical activity intervention effectiveness, impacting in several interacting ways. Conceptualization: Current programs focus on tightly-constructed content that ignores the context in which the program will be delivered, thereby limiting effectiveness. We propose a move away from uniform interventions that maximize internal validity towards a flexible approach that enables schools to tailor content to their specific context. Evaluation designs: Evaluation of context-specific interventions should explicitly consider context. This is challenging in cluster randomized controlled trial designs. Thus, alternative designs such as natural experiment and stepped-wedge designs warrant further consideration. Primary outcome: A collective focus on average minutes of moderate to vigorous intensity physical activity may not always be the most appropriate choice. A wider range of outcomes may improve children’s physical activity and health in the long-term. In this paper we argue that greater consideration of school context is key in the design and analysis of school-based physical activity interventions and may help overcome existing limitations in the design of effective interventions and thus progress the field. While this focus on context-specific interventions and evaluation is untested, we hope to stimulate debate of the key issues to improve future physical activity intervention development and implementation.